If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(2x + -1)(3x + 2) = 0 Reorder the terms: x(-1 + 2x)(3x + 2) = 0 Reorder the terms: x(-1 + 2x)(2 + 3x) = 0 Multiply (-1 + 2x) * (2 + 3x) x(-1(2 + 3x) + 2x * (2 + 3x)) = 0 x((2 * -1 + 3x * -1) + 2x * (2 + 3x)) = 0 x((-2 + -3x) + 2x * (2 + 3x)) = 0 x(-2 + -3x + (2 * 2x + 3x * 2x)) = 0 x(-2 + -3x + (4x + 6x2)) = 0 Combine like terms: -3x + 4x = 1x x(-2 + 1x + 6x2) = 0 (-2 * x + 1x * x + 6x2 * x) = 0 (-2x + 1x2 + 6x3) = 0 Solving -2x + 1x2 + 6x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-2 + x + 6x2) = 0 Factor a trinomial. x((-2 + -3x)(1 + -2x)) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-2 + -3x)' equal to zero and attempt to solve: Simplifying -2 + -3x = 0 Solving -2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -3x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -3x = 0 + 2 -3x = 0 + 2 Combine like terms: 0 + 2 = 2 -3x = 2 Divide each side by '-3'. x = -0.6666666667 Simplifying x = -0.6666666667Subproblem 3
Set the factor '(1 + -2x)' equal to zero and attempt to solve: Simplifying 1 + -2x = 0 Solving 1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 0 + -1 -2x = 0 + -1 Combine like terms: 0 + -1 = -1 -2x = -1 Divide each side by '-2'. x = 0.5 Simplifying x = 0.5Solution
x = {0, -0.6666666667, 0.5}
| x^4-24x^3+144x^2=0 | | 8+2x+3-x=2x-1 | | 4x-12x+9=0 | | x^4-24x^3+14x^2=0 | | -39+r=26 | | =4y^3-4y^2+3-y | | 11-8x=147-36x | | (7x^2)+24=54 | | x^3+x=332.5 | | (20+p)+(3p-23)+p=552 | | 11x=3x^2-4 | | 45=3(w-36)+30 | | X+x+12+x+x+12=x+11+x+11+x+16 | | 4(k+10)+k= | | x^2+12=-9 | | 3(5x+4-2x)+5(3x-9)=2(8x-1)+3-9x | | 11*-7+12=x | | (12y+12)-21y= | | 8*-7-9=x | | -23-4x=-27 | | x-2x+x^2=20 | | -5(5a-3)-14a=-24 | | x+(x+13)+(2x-15)=470 | | -4y-3(2y+3)=-3 | | 98/4 | | a=-0.8(20)+54 | | 50-12+4=x | | -7r=48 | | (x+x^2)+20=2x | | E+19=e-11 | | 4y^3-y^2+6y=0 | | 5k-12=2k |